Facile fabrication of superhydrophobic and superoleophilic green ceramic hollow fiber membrane derived from waste sugarcane bagasse ash for oil/water separation - Jamalludin, Mohd Riduan; Hubadillah, Siti Khadijah; Harun, Zawati; Othman, Mohd Hafiz Dzarfan; Yunos, Muhamad Zaini; Ismail, Ahmad Fauzi; Wan Salleh, Wan Norharyati (Elsevier, 2018)
Green ceramic hollow fiber membranes with superhydrophobic and superoleophilic surfaces (ss-CHFM/WSBA) were successfully fabricated via facile sol–gel process using tetraethoxysilane (TEOS) and methyltriethoxysilane (MTES) as precursors. In this work, silica solution was prepared using the modified Sto¨ber method. This process was followed by dipping the pristine membranes into the sol–gel solution at various grafting times (0–90 min), grafting cycles (0–4 cycles), and calcination temperatures (400–600⁰ͦC). The wettability, surface morphology, and chemical composition of the pristine and ss-CHFM/WSBA membranes were investigated. The results showed that increasing the grafting time has increased the wettability of ss-CHFM/WSBA with high contact angle of up to 163.9⁰. Similarly, increasing grafting cycle has enhanced the hydrophobicity of ss-CHFM/WSBA due to the formation of hierarchical structure of grafting cycle which were more than one. The optimum calcination temperature for ss-CHFM/WSBA was identified. It was found that increasing the calcination temperature has degraded the sol template on the surface of ss-CHFM/WSBA, hence decreasing the wettability. The preliminary performance tests showed that ss-CHFM/WSBA grafted at 60 min, 3 cycles, and calcined at 400 ⁰C showed excellent oil/water separation efficiency of 99.9% and oil flux of 137.2 L/m2 h.